Nasionalisme: Kajian Novel A. Hasjmy - Wildan Wildan (Kedeputian Bidang Ilmu Sosial dan Kemanusiaan (IPSK-LIPI), 2010)
This study is about nationalism that has been portrayed in seven novels written by A. Hasjmy, an Acehnese writer. The novels are Melalui Jalan Raya Dunia (1938), Bermandi Cahaya Bulan (1939), Suara Azan dan Lonceng Gereja (1940), Nona Pressroom (1951), Elly Gadis Nica (1951), Meurah Djohan: Sultan Aceh Pertama (1976), and Tanah Merah: Digul Bumi Pahlawan Kemerdekaan Indonesia (1976). The aim of the study is to analyze nationalism compatibility in the context of Indonesian politics. There are two types of nationalism in Indonesia. Firstly, nationalism for the nation-state of Indonesia, and secondly parochial nationalism held by the separatist movements at the provincial level and in this case the Acehnese nationalism. This is studied by examining the elements of nationalism, such as doctrines and missions put forward in the novels and the techniques of writing used by the writer. This is a qualitative research in which the data has been obtained through library research and interviews. The main finding of this study shows that Indonesian nationalism is obviously well represented in the novels. This finding is contrary to the public opinion that most of the Acehnese are supporters of the separatist movement, i.e. Acehnese nationalism. Thus, in portraying the nationalism, A. Hasjmy has exploited certain writing techniques in his novels, such as epistolary, speeches, diary, poems and footnotes to camouflage its doctrines and missions. With these findings, the significance of this study is that it could elucidate academically that not every Acehnese agrees with the idea of freedom of Aceh from Indonesia Raya.Keywords: nationalism, novel, A. Hasjmy, Acehnese